2022
DOI: 10.4085/1062-6050-0346.21
|View full text |Cite
|
Sign up to set email alerts
|

Playing Position and the Injury Incidence Rate in Male Academy Soccer Players

Abstract: Context: It is unclear whether playing position influences injury in male academy soccer players (ASP). Objective: To determine if playing position is associated with injury in ASP. Design: Descriptive Epidemiology Study. Setting: English, Spanish, Uruguayan and Brazilian soccer academies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…As an example, this study showed that the highest injury occurred to the defender (35%), while the lowest position was a goalkeeper (11%). Interestingly, this finding differs from the research revealed by Hall et al (2022). In their context, the most vulnerable position in the football academy was a midfielder at 8.67/1000 hours.…”
Section: Discussioncontrasting
confidence: 83%
“…As an example, this study showed that the highest injury occurred to the defender (35%), while the lowest position was a goalkeeper (11%). Interestingly, this finding differs from the research revealed by Hall et al (2022). In their context, the most vulnerable position in the football academy was a midfielder at 8.67/1000 hours.…”
Section: Discussioncontrasting
confidence: 83%
“…Consequently, team success is associated with low injury rates [127], having more players available for matches and training [128], and losing fewer days to injury during a season [18]. Despite scientific advances identifying a number of risk factors, including player age, previous injury and joint range of motion [1], as well as maturity status [24], playing position [23] and biological sex [129],…”
Section: The Genetic Association With Injury Risk In Soccer Playersmentioning
confidence: 99%
“…Conse quently, team success is associated with low injury rates [127], hav ing more players available for matches and training [128] and los ing fewer days to injury during a season [18]. Despite scientific ad vances identifying a number of risk factors, including player age, previous injury, and joint range of motion [1] as well as maturity status [24], playing position [23], and biological sex [129], inter individual variation in the frequency and severity of soccer injury suggests not all factors are fully understood. With injury preven tion representing a key objective for players and coaches, it is logi cal that athletes and practitioners believe there may be value in ge netic data concerning injury susceptibility [130], not least because previous injury increases future injury risk [1].…”
Section: The Genetic Association With Injury Risk In Soccer Playersmentioning
confidence: 99%
See 2 more Smart Citations